2011
DOI: 10.1177/0149206310394864
|View full text |Cite
|
Sign up to set email alerts
|

Reconsidering Work—Family Interactions and Satisfaction: A Meta-Analysis

Abstract: Researchers studying work—family conflict, and to a lesser extent work—family enrichment, have often relied on Frone, Russell, and Cooper’s domain specificity model to explain the relationships between bidirectional work—family interactions and family and job satisfaction. However, in more recent times, theorists have proposed an alternative model, the source attribution perspective, which predicts a different pattern of relationships. Using meta-analytic path analysis, the present study compared competing hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
275
2
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 374 publications
(305 citation statements)
references
References 126 publications
24
275
2
4
Order By: Relevance
“…For example, we found that the common predictors of workfamily conflict and work engagement displayed moderate to strong relationships with common outcomes such as work satisfaction, general health, and burnout, which were similar in magnitude to published meta-analyses (cf. Nahrgang et al 2011;Reichl et al 2014;Shockley and Singla 2011) and primary studies (e.g., Grawitch et al 2013;Matthews et al 2014a;Wayne et al 2017). These results suggest a high level of data quality and potential validity of inferences for organizational and occupational health research via MTurk assuming methodological concerns and validity threats are addressed (for recommendations see Cheung et al 2016).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…For example, we found that the common predictors of workfamily conflict and work engagement displayed moderate to strong relationships with common outcomes such as work satisfaction, general health, and burnout, which were similar in magnitude to published meta-analyses (cf. Nahrgang et al 2011;Reichl et al 2014;Shockley and Singla 2011) and primary studies (e.g., Grawitch et al 2013;Matthews et al 2014a;Wayne et al 2017). These results suggest a high level of data quality and potential validity of inferences for organizational and occupational health research via MTurk assuming methodological concerns and validity threats are addressed (for recommendations see Cheung et al 2016).…”
Section: Discussionmentioning
confidence: 81%
“…These effects were similar in magnitude to published meta-analyses on the outcomes of work-family conflict. For example, the most comprehensive meta-analysis on the topic found work-to-family conflict and job satisfaction had an average uncorrected relationship of r = −.25 (95% CI = −.27, −.23) across studies (Shockley and Singla 2011). Meanwhile, a recent metaanalysis by Reichl et al (2014) found an average uncorrected relationship of r = .51 and an unreliability corrected relationship of ρ = .61 (95% CI = .58, .63) between work-tononwork conflict and emotional exhaustion (a core component of the SMBM used in the current study).…”
Section: Resultsmentioning
confidence: 99%
“…A substantial body of empirical research has identified its antecedents and consequences (e.g. Carlson et al, 2010;Chen et al, 2016;McNall et al, 2010;Shockley and Singla, 2011). These studies have enhanced our understanding of enriching processes between work and family in single countries and cultures.…”
Section: Introductionmentioning
confidence: 99%
“…Byron, 2005;Eby et al, 2005;Ford et al, 2007;Shockley and Singla, 2011). However, crossnational/cultural research on these areas is limited (see Rajadhyaksha et al, 2015, for a recent overview).…”
Section: Introductionmentioning
confidence: 99%
“…Il a, par la suite, été démontré que cette relation est bidirectionnelleles interférences du travail sur la famille (ITF) et de la famille sur le travail (IFT) -et que ces deux directions sont spécifiques en termes d'antécédents et de consé-quences (Amstad et al, 2011;Byron, 2005;Shockley et Singla, 2011). Alors que les interférences tirent leur origine de la sphère familiale ou de la sphère professionnelle, leurs conséquences pourraient être associées aux deux domaines de vie.…”
unclassified